Characterization of periwinkle genotypes through DUS test - PATEL, TEJAL; PATIL, SUDHA; CHAWLA, S. L.; BHATT, DIPAL (Journal of Ornamental Horticulture, 2025)
Catharanthus roseus has been reported to be very useful for the various medical and neutraceutical application besides its ornamental value. Information on morphological characters of periwinkle is needed for development and improvement of this plant species so that its full potential can be optimally utilized. This high diversity germplasm was obtained through exploration efforts. To be successfully utilized in plant breeding programs, the germplasm must be identified for the important characters and expected to have a broad diversity. As a result, an attempt was undertaken to characterize 11 periwinkle genotypes in order to produce identifying keys that are reliable and reasonably straightforward to conduct when applying DUS (distinctness, uniformity and stability) testing. However, distinct differences were noticed in vegetative and floral characters. The study on periwinkle genotypes has successfully demonstrated that all the genotypes differed significantly, which makes the candidate genotype eligible to seek protection in future. The present study therefore provides very useful leads for future research efforts in this direction.